'Nasal mask’ in comparison with ‘nasal prongs’ or ‘rotation of nasal mask with nasal prongs’ reduce the incidence of nasal injury in preterm neonates supported on nasal continuous positive airway pressure (nCPAP): A randomized controlled trial - Bashir, Tanveer (PLoS One, 2019)
BACKGROUND: With increasing use of nCPAP, the safety and comfort associated with nCPAP have come into the forefront. The reported incidence of nasal injuries associated with the use of nCPAP is 20% to 60%. A recent meta-analysis concluded that the use of nasal masks significantly decreases CPAP failure and the incidence of moderate to severe nasal injury and stress the need for a well powered RCT to confirm their findings. METHODS: In this Open label, 3 arms, sequential, stratified randomized controlled trial, we evaluated the incidence and severity of nasal injury at removal of nCPAP when using two different nasal interfaces and in three groups (i.e. rotation group, mask continue group, prong continue group). Preterm infants with gestation ≤ 30 weeks and respiratory distress within the first 6 hours of birth and in need of CPAP were eligible for the study. RESULTS: Among the 175 newborns included in the study, incidence of nasal injury in mask continue group [n = 19/57 (33.3%)] was significantly less as compared to prong continue group [n = 55/60 (91.6%)] and rotation group [33/ 58 (56.9%), p value <0.0001]. Median maximum nasal injury score was significantly less in Mask continue group as compared to Prong continue group and Rotation group [Injury Score 0 (IQR 0–1) vs. Injury Score 3 (IQR 2–5) vs. Injury Score 1 (IQR 0–2), p value = <0.0001] respectively. The proportion of infants failing nCPAP was similar across the three groups. CONCLUSION: nCPAP with nasal masks significantly reduces nasal injury in comparison with nasal prongs or rotation of nasal prongs and nasal masks. However, the type of interface did not affect the nCPAP failure rates.